2022
DOI: 10.1021/acs.est.2c03769
|View full text |Cite
|
Sign up to set email alerts
|

Surface Boronizing Can Weaken the Excitonic Effects of BiOBr Nanosheets for Efficient O2 Activation and Selective NO Oxidation under Visible Light Irradiation

Abstract: The photocatalytic O 2 activation for pollutant removal highly depends on the controlled generation of desired reactive oxygen species (ROS). Herein, we demonstrate that the robust excitonic effect of BiOBr nanosheets, which is prototypical for singlet oxygen ( 1 O 2 ) production to partially oxidize NO into a more toxic intermediate NO 2 , can be weakened by surface boronizing via inducing a staggered band alignment from the surface to the bulk and simultaneously generating more surface oxygen vacancy (V O ).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 94 publications
(50 citation statements)
references
References 39 publications
(58 reference statements)
1
38
0
Order By: Relevance
“…Furfuryl alcohol (FFA) and nitrotetrazolium blue chloride (NBT) were then adopted as probe molecules to quantify the ·O 2 – and 1 O 2 yields, respectively (Figure S29). In agreement with EPR results, the accumulated 1 O 2 in BiOBr (0.38 μM) after 60 min of light irradiation was 9.5 times that of BiOBr-A (0.04 μM), while the ·O 2 – yield of BiOBr-A (2.27 μM), in turn, was 3.5 higher than that of BiOBr (0.51 μM). To this end, excitons in BiOBr could easily activate O 2 through energy transfer to generate 1 O 2 , while photoelectrons arisen from the robust exciton dissociation in BiOBr-A were supposed to dominate O 2 activation to ·O 2 – .…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Furfuryl alcohol (FFA) and nitrotetrazolium blue chloride (NBT) were then adopted as probe molecules to quantify the ·O 2 – and 1 O 2 yields, respectively (Figure S29). In agreement with EPR results, the accumulated 1 O 2 in BiOBr (0.38 μM) after 60 min of light irradiation was 9.5 times that of BiOBr-A (0.04 μM), while the ·O 2 – yield of BiOBr-A (2.27 μM), in turn, was 3.5 higher than that of BiOBr (0.51 μM). To this end, excitons in BiOBr could easily activate O 2 through energy transfer to generate 1 O 2 , while photoelectrons arisen from the robust exciton dissociation in BiOBr-A were supposed to dominate O 2 activation to ·O 2 – .…”
Section: Resultssupporting
confidence: 88%
“…Meanwhile, the [Br] − slabs with highly localized valence electrons display reduced electronic screening that further makes e – –h + pairs strongly tangled in energy, eventually evolving into excitons (Scheme b). To this end, strong excitonic effects in layered BiOBr with highly ordered out-of-plane symmetry constitute shackles for charge carrier-driven photocatalysis, including O 2 activation , and CO 2 reduction . The introduction of defects, , dopants, ,, and disordered domains into exciton-based 2D layered photocatalysts has been previously demonstrated to enable destabilization of bound excitons via establishing discontinuously distributed energy landscapes, thus promoting exciton dissociation.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is highly desirable to design and explore photocatalysts exhibiting high efficiency for NO conversion and inhibiting toxic byproduct yields to avoid secondary pollution. Witnessed efforts demonstrate that microstructure controlling, e.g., strengthening surface–interface interaction and promoting carrier separations on pure photocatalyst, is the most ideal and useful method to enhance reaction efficiency, which is still mostly desired and challenging. …”
Section: Introductionmentioning
confidence: 99%
“…This indicated that COF-DBT with double donor units contained more free electrons in the COF skeleton than COF-DT with a single donor unit, which confirmed that COF-DBT had a stronger electron-donating capacity than COF-DT. 66 Clearly, strengthening D−A interactions via increasing the donor unit number from one to two could reduce the E b and improve the IRCT process in COFs, leading to the improvement of exciton dissociation and charge transfer. Therefore, via the significant improvement of the photogenerated charge separation efficiency, COF-DBT with double donor units could exhibit efficient photocatalytic pollutant elimination performance with light irradiation.…”
Section: Degradation Performance Toward Different Types Of Emerging C...mentioning
confidence: 99%